(3eY GdTjN GdTYQGhjs (3hbaGJ EjeGfjI hMce NGdOIs - (3fLe, GdSjOs; (3ShGM, SGde YHO GdeYRs ((3GdbGgQIs (3OGQ RMeI ocnJGH ddfTQ hGdJhRjYs, 2025)
(3GdcJGH gh fGaPI eTQbI Ydi YGde GdEjeGf hGdMceI MjK JScf cdeGJ GdTjN GdTYQGhj GdJj JMed YHb GdJOHQ GdbQBfj hQhMGfjI GdJacQ aj eYGfj GdMjGI HCSdhHg GdYejb hGdHSjW aj Bf hGMO, jbOe GdJGH OQhSG NGdOI JbhO GdbGQF Edi age CYeb dYXeI GdNGdb hMbGFb GdhLhO eY Mce hhbaGJ JQJbj HGdbdH hJZPj GdQhM, Efg cJGH dcd ef jSYi Edi fhQ jHOO XdeGJ GdWQjb hjhbX aj OGNdg TYdI Gdjbjfs
1
Keywords: (3eMeO eJhdj GdTYQGhjs; (3GdhYX hGdEQTGOs